Aplikasi Teknologi Radiasi Panas Pada Pengolahan Sawit Terpadu. (APPLICATION OF HEAT RADIATION TECHNOLOGY IN THE INTEGRATED PALM OIL PROCESSING) - Amos Lukas; Suharto Ngdiwaluyo; Ishenny Mohd Noor; Natsir La Teng (Balai Besar Industri Hasil Perkebunan, 2017)
This article review application of heat radiation technology in the integtated palm oil processing, which has been developed by Ishenny and Noor (2015,Ishenny) . This technology named as Palm Oil Mill Heat Radiation Technology uses direct heat radiation (with palm fruit buch waste as the fuel), instead of heat from steam boilers, as in the conventional technology. Temperature and pressure of the cooking chamber are designed at 150° C and 1 atm. Compared to the conventional technology, this new technology is more profitable because it could process all parts of the palm fruits to produce red oil, fatty oil, kernel oil (three with higher qualities), biochar, liquid smoke, and cake, releases relatively no waste, and could operate even at a low capacity. In addition, this new technology could be implemented to modify the conventional technology used at present in the palm oil plants. Estimated investment required for processing 45 ton per hour of palm fruits is IDR 300 billions. Net profit a year is estimated IDR 230 billions with ROI of 1.94 year.Keywords : Innovation of palm oil factory, palm oil, red oil, kernel oil, fatty oil, 7 MW electricity, liquid smoke, kernel cake and biocharAbstrak. Artikel ini mengulas aplikasi teknologi radiasi panas pada pengolahan sawit terpadu yang telah dikembangkan oleh Ishenny dan Noor (2015, Ishenny). Teknologi ini yang dinamai Palm Oil Mill Heat Radiation Technology menggunakan panas radiasi langsung (dengan bahan bakar limbah tandan buah kosong), tidak seperti pada teknologi konvensional yang menggunakan panas dari ketel uap. Suhu dan tekanan pada panci masak dirancang sebesar 150° C dan 1 atm. Dibandingkan dengan teknologi minyak sawit konvensional, teknologi baru ini lebih menguntungkan, karena dapat memproduksi minyak merah, minyak lemak, kernel oil (ketiganya dengan mutu yang lebih tinggi), biochar, asap cair, dan bungkil, relatif tanpa limbah, dan dapat beroperasi pada kapasitas yang kecil. Disamping itu, teknologi ini dapat diaplikasikan untuk memodifikasi teknologi konvensional yang saat ini digunakan oleh pabrik minyak sawit. Estimasi investasi yang diperlukan untuk mengolah 45 ton per jam buah sawit segar adalah Rp. 300 milyar, dengan estimasi keuntungan Rp. 230 milyar per tahun dan ROI 1,94 tahun.Kata Kunci : Inovasi pabrik kelapa sawit, minyak sawit, minyak merah, minyak inti, minyak lemak, li strik 7 MW, asap cair, kernel dan bokar